Implementasi Gerakan Perilaku Hidup Bersih dan Sehat serta Protokol Kesehatan Pada Santri di Masa New Normal - Eka Sakti Wahyuningtyas; Erni Yuliati; Nur Wahyuni; Erni Rubiyati; Yuliyah (Yayasan Inspirasi El Burhani, 2022)
Introduction: Currently, the COVID-19 virus has a new variant, namely Omicron, where transmission is faster than other variants. One of the ways to prevent COVID-19 is through clean and healthy living behavior by washing hands with proper soap (acidabun) and following health protocols. Disobedience to PHBS and health protocols risks the spread of COVID-19 very quickly, especially in Islamic boarding schools. The Islamic boarding school in Magelang that is the target of Performing Integrated Community Service (PPMT) is the Tidar Islamic Boarding School. Objective: The purpose of this activity is to identify health problems that are closely related to PHBS, the influence of the PHBS health education, health protocols, proper acidabun training, training to build handwashing facilities in order to prevent covid-19 in the new normal period. Method: The methods used in PPMT activities are: Educational, Community Development is also Participatory. This activity was attended by 40 students from the Tidar Magelang Islamic Boarding School. Result: The results of the activities carried out by PPMT show that there is an increase in knowledge about PHBS and prokes and is expected to be applied in the life of Islamic boarding schools. Conclusion: Health screening can provide an early status of health. Education about PHBS and Health protocol can increase knowledge so that it can be applied in everyday life.